Optimasi Produksi Produk Ayam Katsu dan Siomay Ayam Dengan Metode Goal Programming Menggunakan POM QM for Windows: (Studi Pada Umkm Dapur Mama Cece) - Hidayat, Nurul; Azmi, Nur; Tjia Sunli, Jordan; Asri, Asri (PT. Alahyan Publisher Sukabumi, 2025)
In the face of increasingly fierce competition in the culinary sector, Dapur Mama Cece MSMEs seek to increase efficiency and profitability through optimizing the production process. This study aims to apply the Goal Programming method with the help of POM QM software for Windows to optimize the production of chicken katsu and chicken siomay. This method allows for the analysis of various limiting factors, including the availability of raw materials, production capacity, and fluctuating market demand. The results of the study show that with the implementation of Goal Programming, MSMEs can determine the most efficient production combination, achieve maximum production targets, and minimize waste. In addition, sensitivity analysis provides insight into the impact of variable changes on production output. With this optimization, Dapur Mama Cece can increase competitiveness and meet consumer demands effectively. This research suggests increasing production capacity, better raw material management, and product diversification to support sustainable business growth.